Design and Implementation of a Low Power and Area Efficient Sequential Multiplier - Kumar, Mohit; Yadav, Subhash Chandra (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*280.25px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920649);" role="presentation">A multiplier plays a major role in various digital systems. The area, speed and power consumption of any digital <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*293.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914356);" role="presentation">system, which has a multiplier as its component, depend upon the hardware used for the multiplier. In this paper <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*306.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975018);" role="presentation">we proposed a sequential multiplier which has a lower area requirement and lower power consumption in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*319.85px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917399);" role="presentation">comparison of the conventional sequential multiplier. We can use the proposed system where long battery life is <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*333.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922041);" role="presentation">required and/or reduced hardware is required. The speed of the proposed multiplier is a little bit slower than the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*346.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932902);" role="presentation">conventional one. So we can use the proposed system where long battery life is required and speed is not the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*359.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9144);" role="presentation">major requirement.